Energy optimization of industrial steam boiler using energy performance indicator (2019)
This article shows the application of an energy management system and the calculation of energy efficiency indicators to a pyrotubular boiler, following the guidelines of the ISO50001 standard. The actual energy consumption indicators, the theoretical consumption index, the energy baseline and the efficiency index 100 were evaluated based on gas consumption and steam production data. As for the savings measure, a 20% reduction in gas consumption can be achieved by reducing the operational variability equivalent to 186,633 m3/month, thereby achieving a monthly savings of $70,920,717 COP and a large reduction in natural gas equivalent to a reduction in CO2 emissions (1,318,739.05 kg CO2/month). Also, the purges currently recorded in the boiler are higher than the recommended value for this equipment, and the excess air released varies between 6% and 11%, increasing the losses due to sensible heat. Three main implementations were applied to improve the energy performance of the steam boiler. The first saving implementation was the reduction of the generation pressure from 250 to 180 psig, achieving a lower gas temperature with a reduction of heat losses from the boiler, pipes and steam leakage losses, achieving a saving of 2% of the average natural gas consumption. The second implementation was the automation of the boiler purges, in accordance with the recommended value UNE-9075/85, achieving a total saving of 0.66%, and the third measurement allows on-line correction of the combustion air by direct measurement of O2, which maintains the measured oxygen value at 3%, which is the recommended value. With this practical and novel method energy performance indicator on the boiler, was increased the performance of the equipment, as well as the production costs and environmental impact reduction.